INTERACTIVE POWERPOINTS IN ONLINE TGT-BASED MODELS ON THERMOCHEMICAL MATERIALS - Ratna Kusumawardani; Muhamad Hamami Nata; Iis Intan Widiyowati (Bajang Institute, 2021)
The closure of schools due to the Covid-19 pandemic has forced all schools in Indonesia to be closed temporarily, therefore learning must be carried out online. Online learning is commonly carried out with teacher presentations and assignments therefore this makes learning monotonous and boring for students. So we need a medium that makes learning more interesting, namely with interactive powerpoints. The purpose of this study was to determine the effect of using interactive powerpoints in the online-based TGT model on thermochemistry material. This type of research is quasi-experimental research with a post-test only control group design. The data collection technique used the technique of daily test tests, documentation, and student perception questionnaires. The data were analyzed using the normality test, F test, and t test with a significance level of 5%. The results showed that before being given the treatment, the two classes were normally distributed, homogeneous variations and there was no difference in student absorption. After being given the treatment, the two classes had significant differences in absorption. Therefore it can be concluded that there is an effect of using interactive powerpoints in the online-based TGT model on thermochemistry material.